Prediction of impaired metabolic adaptation by antenatal Doppler studies in small for gestational age fetuses. Issue 7 (July 1992) - Hawdon, J M; Ward Platt, M P; McPhail, S; Cameron, H; Walkinshaw, S A
Abstract : The increased risk of hypoglycaemia for infants who are small for gestational age (SGA) is well known, and further information regarding metabolic adaptation can be gained by examining the profiles of glucose and other metabolic fuels in such infants. Not all SGA infants experience hypoglycaemia, however, and the ability to identify, antenatally, those at most risk would be helpful for obstetric and neonatal management. This study investigated metabolic differences between two groups of SGA infants who had antenatal umbilical artery Doppler studies. Fourteen had end diastolic velocities (EDV) present and 11 had absent EDV. The absent EDV group had significantly lower non-esterified fatty acid (NEFA) concentrations at birth, and lower blood glucose and NEFA concentrations in the first six hours after birth. After the first day, few metabolic differences were found between the two groups. Antenatal Doppler studies may identify those SGA infants who fail to achieve neonatal metabolic adaptation and are most at risk of early neonatal hypoglycaemia.